Politics Before Pupils? Electoral Cycles and School Resources in India - Sonja Fagernäs; Panu Pelkonen (Institute for the Study of Labor (IZA), 2014)
Primary education in India is a development question of a unique magnitude, and the delivery of education by Indian states is often suspected to be marred by political haggling and corruption. Using rich administrative school-level panel data across Indian states, we test for electoral cycles in the provision of school resources. The effects are identified using staggered timing of state elections. We find that rulers allocate more primary school resources in the years preceding and following elections, but there is only weak evidence that resources are targeted to marginal constituencies. The resources affected are visible ones, namely free school uniforms, classrooms, toilets, ramps for the disabled and medical inspections. We also show that around election years, teachers spend more time on "non-teaching" activities. The political cycles are not inevitable, as they are present only in districts characterised by low voter turnout and low female literacy. Finally, we show that electoral cycles affect human capital accumulation: The phase of the electoral cycle in which pupils begin their primary schooling, affects their learning outcomes.
Keywords: H75; I25; O15; P16; 330; institutions; school resources; political cycle; public goods; voter turnout; India